The neuro-ophthalmology survival guide - Pane, Anthony; Burdon, Michael A.; Miller, Neil R. (Philadelphia : Elsevier, 2018)
This book is a practical, symptom-based, 'how-to' guide to neuro-ophthalmology and acquired strabismus for all trainee and practising ophthalmologists. Each chapter focusses on a specific clinical symptom and includes an introduction to the clinical assessment of a symptom; an examination checklist; a management flowchart to be followed; clinical diagnostic criteria checklists; and further information on the diseases that can cause the symptom with a brief discussion of appropriate management -- From publisher website.
Includes bibliographical references (page 365) and index.
Keywords: Eye Diseases; Nervous System Diseases